Contextualization of Photosynthesis Learning Based on Visual Thinking in Elementary Schools: Kontekstualisasi Pembelajaran Fotosintesis berbasis Pemikiran Visual di Sekolah Dasar - Gumilar, Gumgum; Harsono, Harsono; Wulandari, Murfiah Dewi; Markhamah, Markhamah; Rahmawati, Laili Etika (SEJ (Science Education Journal), 2024)
Technology has become an integral part of everyday life, including in education. This study aims to analyze the integration of visual thinking-based contextualization approach in learning photosynthesis material in grade 4 elementary school. Visual thinking helps students understand concepts visually, while the contextualization approach connects academic material with real situations relevant to students. This study used qualitative method with purposive sampling technique. Data was collected through analyzing user responses in the comments column to the types of photosynthesis learning videos found on the YouTube platform such as animated videos, experiments, and scientific presentations. The results of this study show that the variety of video types supports students' learning preferences. Animations facilitate visualization, experiments offer hands-on experience, and scientific presentations deepen concepts. The integration of visual thinking and contextualization creates a positive and interactive learning experience for students.